FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PELAKSANAAN KEGIATAN POSYANDU REMAJA DI PUSKESMAS MUARA ENIM TAHUN 2023 - Andriani, Aminah; Novitry, Fera; Lilia, Deli (Universitas Pahlawan Tuanku Tambusai, 2024)
According to data from the profile of the South Sumatra Regency health service, in 2020 the number of community health centers in Indonesia increased to 9,993 community health centers, of which the number of community health centers providing adolescent health services was 4,835 (48.4%) with the number of youth posyandu being 100,470. This research aims to determine the factors related to the implementation of youth posyandu activities at the Muara Enim health center in 2023. This research uses a quantitative research using a cross-sectional design. The population in this study were all teenagers in the Muara Enim Community Health Center working area, namely 12,152 teenagers and sampling was done using Cluster Random sampling, namely 96 teenagers. The statistical test used in this research is Chi-square. The results of this study state that there is a relationship between knowledge (p= 0.000), distance (p= 0.000), family support (p= 0.000) and social support (p= 0.000) with visits to youth posyandu activities at the Muara Enim health center in 2023. Suggestions for Public health centers in an effort to increase teenagers' interest in participating in posyandu activities need to carry out outreach in the form of health promotion